Under the Deodars - Kipling, Rudyard, 1865-1936 (Salt Lake City, UT : Project Gutenberg, 2001)
"Under the Deodars" by Rudyard Kipling is a collection of short stories published in January 1889. Set primarily in Simla, the British hill station in India, these interconnected tales explore the romantic entanglements, social intrigues, and moral dilemmas of colonial society. From Mrs. Hauksbee's schemes to ambitious flirtations gone awry, forbidden affairs at cemetery rendezvous, and a young subaltern's heroic devotion to his regiment during a cholera outbreak, Kipling captures the passions and pretensions of British India with sharp observation and ironic wit. (This is an automatically generated summary.)
The education of Otis Yeere -- At the pit's mouth -- A wayside comedy -- The hill of illusion -- A second-rate woman -- Only a subaltern -- In the matter of a private -- The enlightenments of Pagett, M.P.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Under_the_Deodars
Release date is 2001-09-01
Produced by and Anonymous Volunteer, and David Widger
Keywords: India -- History -- British occupation, 1765-1947 -- Fiction; Short stories, English